Relationship of Dental Practice with Subjective Happiness and Life Satisfaction - Quratul-Ain-Mariam; Asima Faisal; Muhammad Yahya Noori (JLUMHS, 2021)
OBJECTIVE: To determine association between subjective happiness and life satisfaction with the dental practice among dentists working in Karachi. METHODOLOGY: This cross-sectional study was conducted at the Health Management Department, Institute of Business Management, Karachi on the dentists working under supervision in private and government dental hospitals in Karachi from February - December 2018. Non-probability purposive sampling technique was used and data were collected from 384 dentists. Utrect Work Engagement Scale (UWES) was used to assess work engagement; satisfaction with life was recorded using Satisfaction with Life Scale (SWLS), while subjective happiness was assessed by Subjective Happiness Scale (SHS). Cronbach’s Alpha determined the reliability of the scales used. SPSS Statistics Version 23 (IBM Corp. 2015) was used to analyze the data by applying correlation and multiple linear regression. RESULTS: Majority of the respondents belonged to a younger age group (23-27 years) and the findings showed significantly positive impact of life satisfaction (B=0.98; p< 0.05) and happiness (B=2.32; p< 0.05) on work engagement. Work engagement was found to be positively correlated with life satisfaction and happiness. CONCLUSION: The study concluded that dentists who are satisfied and happy with their lives are found to have a better Work engagement as work engagement was found to be positively correlated with life satisfaction and happiness. However, the impact of life satisfaction on work engagement was relatively found to be greater than the impact of happiness on work engagement.